ENTIRE FUNCTIONS OF STRONGLY BOUNDED L -INDEX IN DIRECTION - Bandura, Andriy Ivanovych; Kulinich, Halyna Mykhailivna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
A concept of entire function of strongly bounded index have been generalized for a multidimensional case. We introduced a class of entire functions of strongly bounded L -index in direction and some properties of this function class are established.